Associação dos ácidos graxos saturados no plasma com índice de massa muscular esquelética apendicular e força em norte-americanos (NHANES 2011- 2012) - Santos, Heitor Oliveira (2023)
Background: The pro-inflammatory potential of saturated fatty acids (SFAs) can hinder skeletal muscle and hence its related parameters. Some research has investigated the association between dietary SFAs and muscle parameters, but little is known about the plasma SFA levels in this regard. Aims: Thus, we aimed to verify the association between plasma SFA levels and muscle parameters (muscle mass and strength) in adults. Methods: A cross-sectional research was performed using the National Health and Nutrition Examination Survey (NHANES) 2011-2012, whereby 937 subjects aged 20-59 and 1591 aged 20-80 years were included for AMMI and muscle strength, respectively. Gas chromatography-mass spectrometry was used to detect plasma total SFAs and their subtypes. Muscle strength was assessed through the sum of handgrip strength. AMMI was calculated by dividing appendicular lean mass by height squared. Linear regression analysis was performed to evaluate the association between SFAs and AMMI adjusting for potential confounders. Results: No association (p-value > 0.05) was observed between plasma total SFAs and their subtypes (capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, margaric acid, pentadecanoic acid, arachidic acid, tricosanoic acid, lignoceric acid, and docosanoic acid) with AMMI (adjustments for energy and protein intakes, smoking, family income, diabetes, hypertension, alcohol, marital status, education level, arthritis, fat mass, physical activity, age, sex, and race). Plasma total SFAs and their individual types were not associated with handgrip strength (adjustments for energy intake, protein intake, smoking, family income, diabetes, arterial hypertension, alcohol, marital status, education level, arthritis, physical activity, age, sex, race, and body mass index), however, when subjects were divided according to age, negative associations were observed for capric acid (β-value = -0.2978; 95%CI = -0.5855, -0.0100; p = 0.043) and stearic acid (β-value = -0.0058; 95%CI = -0.0100, -0.0003; p = 0.038) levels only for those aged <60 years. Conclusion: Overall, plasma total SFAs and their types are not associated with AMMI and muscle strength in Americans. We only observed an inverse association for muscle strength with stearic acid and capric acid for those aged <60 years.